Water holding capacity of two olive (Olea europea L.) cultivars in Cañete valley, Lima-Peru - Borjas, Ricardo (2015)
The study of the indexes of water to Olea europea L. is important because it allows understanding of the water capacity of this species. This trial was carried out in the Valley Cañete with olive varieties ‘Frantoio’ and ‘Sevillana’ (both 10 years old), with the aim of determine its moisture content. In both varieties relative water content (CHR), the Content of water saturation (CAS), the water deficit for saturation (DAS), dry weight (PS) and fresh weight (FW) was measured. ‘Sevillana’ shown a CHR (73.7%), PS (0.180 g) and PF (0.330 g) were higher than in the cultivar 'Frantoio' (with values of 68.2%, 0.140 g and 0.258 g respectively). In conclusion, these results indicate that the variety ‘Sevillana’ has greater capacity than water ‘Frantoio’ to withstand arid environments.